Mucosal Vaccine for Prevention of Viral Disease in Animal - ., Sudarisman (Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
The major obstacle in combating infectious viral diseases in animals is the lack of effective vaccines . A large number of viral pathogens are mucosaly transmitted and must cross mucosal barriers to infect the host . The mucosal surfaces of the gastrointestinal and respiratory tracts represent the principal portals of entry for most animal viral pathogens . Current inactivated viral vaccines administered by intramuscular injection elicit primarily circulating antibodies . The best defense against these predominantly mucosal viral pathogens would be vaccines capable inducing both systemic and mucosal immunity which is a cost effective disease prevention tool . For most viral pathogens, induction of mucosal immunity appears most appropriate based on the routes of infection . The effectiveness of vaccine delivery to mucosal surfaces including respiratory tract may be most useful for prevention of the upper ways where secretory antibody is most important for protection against viral infection . Most external mucosal surfaces are replete with organized follicles and scattered antigen-reactive or sensitized lymphoid elements, including B cells, T lymphocytes, T cell subsets . plasma cells and a variety of other cellular elements involved in the induction and maintenance of immune response . Thus, a better understanding of the mucosal immune system is needed before effiective mucosal vaccines can be developed. Key words : Viral disease. mucosal vaccine